The study of fire safety for multi-storey container hotel: a case study in Muar PPT hotel - Hanapi, Nur Amalina; Idris Shazali, M. Azzamudeen; Abd Wahab, Izudinshah; Ahmad Mahmud, Nasrul Arif
Recent trends show diversified usage of container that usually intended as mobile transportation case for trading industry and now applied as building materials especially for commercial building such as hotel. However, as new material, it should comply with basic fire safety requirement which spelled out in the Uniform Building By-Laws (UBBL) 1984. In the construction laws of a building in Malaysia, the characteristics of building must comply with the requirement and regulations before it is being approved in the Certificate of Completion and Compliance (CCC). Thus, this study is focusing on the container materials and its compliance of fire safety requirements and strategies for multi-storey container hotel building. Literature review and case study are used in order to get the information and to compare the ability of the materials and construction to comply with UBBL 1984 in terms of passive design. The results of the evaluation show the possibilities of Multi-Storey Container Hotel to be built and used complied with passive fire safety requirement.